Singapore Teachers : SABER Country Report 2015 - Joo, Lim Kek (World Bank, Washington, DC, 2018)
This report presents the results of the SABER-Teachers tool as applied in Singapore. A collaborative effort between the UNESCO International Task Force on Teachers for Education 2030 and the World Bank Group's SABER-Teachers initiative made this report possible. All data collection, related analysis, and report preparations were completed by UNESCO using the World Bank Group's SABER tools. The report describes the performance of Singapore's education system in achieving each of the eight teacher policy goals. It also contains comparative information from education systems that have consistently scored highly on international student achievement tests and those that have previously participated in the SABER-Teachers initiative. This report has been formally endorsed by the Ministry of Education of Singapore. Additional information on the teacher policies in the education systems of Singapore and other countries can be found on the SABER-Teachers' website.